Electrowetting-based beam scanner with controllable field of view - Zhao, Rui; Zhang, Kai; Kou, Songfeng; Wei, Xian; Liang, Zhongcheng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
A beam scanner based on electrowetting with controllable field of view is designed. Depending on the first-order paraxial approximation, the scanning path and scanning radius of the beam scanner are derived. Its physical model and properties are established and analyzed with the help of by using the COMSOL and MATLAB. The results show that the scanning beam emitting from the beam scanner realizes 360° scanning freely, and its controllable field of view varies from 0 to 65.3 m successfully under the action of working voltage. The two liquid interfaces in the beam scanner can rotate clockwise or counterclockwise independently, and their inclination angle ranges from 0° to 45°. When the two liquid interfaces turn in the same direction, the scanning effect of edge field is better than that of the central zone. While the scanning effect of the central area is greatly improved and better than that of the edge field when the two liquid interfaces turn in the different direction. In addition, the rotation frequencies of the two interfaces affect the performance of the beam scanner.
Optica Applicata, Vol. 53, 2023, nr 4, s. 655-665
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; beam scanner; electrowetting; controllable field of view; COMSOL; MATLAB